The Role of Carotid Intima-Media Thickness in Carotid Ultrasound Screening - Hyangkyoung Kim (Journal of Surgical Ultrasound)
Carotid ultrasound is a widely utilized, non-invasive diagnostic tool primarily performed to detect significant carotid artery stenosis, and thus, to prevent cerebrovascular events using primary and secondary prevention strategies, while also serving as an important measure of future cardiovascular risk. This imaging modality is particularly valuable for identifying asymptomatic individuals with high-grade stenosis who might benefit from timely medical or surgical intervention to reduce the risk of ischemic stroke. Carotid ultrasound provides critical information on systemic atherosclerosis and prognostic information relevant to overall cardiovascular health. In addition, carotid intima-media thickness (CIMT) is considered a reliable marker for assessing subclinical atherosclerosis and stratifying cardiovascular risk, and high-resolution ultrasound CIMT measurements enable the early detection of atherosclerotic changes, even in individuals without overt clinical symptoms. This review explores the multifaceted utility of carotid ultrasound, emphasizes its roles for primary prevention in high-risk populations and secondary prevention in patients with established cardiovascular disease, and its broader application for CIMT-based cardiovascular risk stratification.